Migration and season explain tick prevalence in Brazilian birds. Issue 4 (20th May 2021) - Fecchio, A.; Lugarini, C.; Ferreira, A.; Weckstein, J. D.; Kuabara, K. M. D.; De La Torre, G. M.; Ogrzewalska, M.; Martins, T. F.; de Angeli Dutra, D.
Abstract: Neotropical birds are mostly parasitized by immature ticks and act as reservoir hosts of tick‐borne pathogens of medical and veterinary interest. Hence, determining the factors that enable ticks to encounter these highly mobile hosts and increase the potential for tick dispersal throughout migratory flyways are important for understanding tick‐borne disease transmission. We used 9682 individual birds from 572 species surveyed across Brazil and Bayesian models to disentangle possible avian host traits and climatic drivers of infestation probabilities, accounting for avian host phylogenetic relationships and spatiotemporal factors that may influence tick prevalence. Our models revealed that the probability of an individual bird being infested with tick larvae and nymphs was lower in partial migrant hosts and during the wet season. Notably, infestation probability increased in areas with a higher proportion of partial migrant birds. Other avian ecological traits known to influence tick prevalence (foraging habitat and body mass) and environmental condition that might constrain tick abundance (annual precipitation and minimum temperature) did not explain infestation probability. Our findings suggest that migratory flyways harbouring a greater abundance of migrant bird hosts also harbour a higher prevalence of immature ticks with potential to enhance the local transmission of tick‐borne pathogens and spread across regions. Abstract : Prevalence of immature tick increases during the dry season in Brazilian wild birds. Partially migratory birds were less likely infested by tick compared to resident bird species. Migratory flyways with a greater proportion of migrant bird harbour a higher prevalence of immature ticks with potential to enhance the local transmission of tick‐borne pathogens and spread across regions.